使用手势法提高以马内利二校中专一年级学生分辨汉语四声的能力 - Wandika Wandika; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2020)
Absract In the learning process. every students will face some difficulties. One of the difficulties happened in the teaching learning process is when the students read some vocabularies. The students just read the vocbularies, but the students did not know how to pronounce in the first tone, second tone, third tone and fourth tone. Infact, there are some students did not khow about it. The fourth tone in mandarin language is the importent thing when the students want to pronounce a word or a sentence. This reseach is aim was to know can the body language method imporov students’ ability in differentiating of fourth tone in mandarin language.The researcher analyzed the result of observation toward the use of body language method to imporov students’ ability in differentiating of fourth tone in mandarin language. The sample of this research was the tenth grade marketing 2 students and the tenth grade accounting 1 students of SMK Kristen Immanuel II. The observation showed that the use of body language method can imporov the students’ ability in differentiating of fourth tonein mandarin language. This research proved that body language method is suitable to use in the teaching learning process. Key word: Body language method，Differentiating ability, Fourt tone of mandarin